Análise do perfil protéico do intestino médio de machos e fêmeas de Anopheles darlingi Root, 1926 (Diptera: Culicidae), em diferentes condições alimentares - Pereira, Kely Lima (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
The malaria is an infectious disease, caused by unicellular parasites of the genus Plasmodium and transmitted by mosquitoes of the genus Anopheles. In the Amazon, the A. darlingi is the main vector of the malaria. It is in the medium intestine of the mosquito that many of the protein reactions occur after the ingestion of different foods. Therefore, the objective of this study was to analyze the proteins in the medium intestine of the main vector mosquitoe of malaria in Brazil, comparing the protein s profile between males and females in different alimentary conditions. Larva was collected in natural nurseries and maintained at the laboratory until the adults emerged and were identified. These were fed with glucose or blood, followed by dissection after 19:00 and 24:00 hours respectively, in lid PBS containing proteases inhibitors. The extraction of proteins was accomplished being used ultrasound in bath of ice, following by precipitation with TCA and analyzed by eletroforese in gel desnaturante (SDS-PAGE) and two-dimensional eletroforese. It was observed in the females that the head office peritrófica was completely formed in 24:00 after the sanguine feeding. The results indicated some spots of proteins with comparative profiles between males and females of A. darlingi suffered influence of the feeding type and other spots met preserved in the two sexes independent of the feeding type. The spots number with profile of comparable migration obtained in males and females fed with glucose was 21, for females fed with blood and glucose was of 20 and, for males and females blood, it was 26. The number of spots constituent protéicos of the species was 18, while spots of proteins of dependent females of the glucose feeding was same to 10, spots protéicos of dependent females of the sanguine feeding was only same to 14 and 10 spots present protéicos in the intestine in males.
Keywords: Matriz Peritrófica; Alimentação sanguínea; Malária